CHRONOTHERAPEUTIC DRUG DELIVERY SYSTEM: AN EMERGING APPROACH TO TREAT CIRCADIAN RHYTHMIC RELATED DISEASE - Kuila, Anuttam; Dhandapani, Nagasamy Venkatesh; Bhowmik, Himangshu; Soni, Abhishek; Kumar, Kammari Harish (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The research on chronotherapy has garnered interest from scientists to understand circadian rhythms and their applications in the biological system. The area of chronotherapeutics covers essential information which is helpful to move forward and solve entanglements in current drug delivery technology. Chronotherapy is the conveying drugs in the body at the target site by maintaining perfect synchronicity with circadian rhythms. The main aim of the current rhythmic research is to formulate and design a therapeutic novel system which can deliver the drug in a desired way inside the body to treat various rhythmic diseases according to their occurrence. Drug release from an ideal chronotherapeutic system should be rapid, and the release of drug from the delivery system should also be complete after a specific or defined lag time period. Recently, scientists are involved in developing chronotherapeutic drug delivery system to treat chronological diseases such as single and multiple units using an erodible, soluble or insoluble polymer coating, and stimuli regulated drug delivery systems. In this review, we focus on the elaboration of the concept of chronotherapy, main challenges ahead during its development process, current approaches and its future applications in drug delivery in the treatment of circadian rhythmic diseases.